Things to keep in mind after cardiopulmonary resuscitation: bilateral severe and widespread subcutaneous emphysema together with unilateral pneumothorax - Alar, Timuçin; Gedik, İsmail Ertuğrul (The European Research Journal, 2019)
Cardiopulmonary resuscitation (CPR) can cause severe complications such as rib and sternal fracture, pneumothorax or hemothorax. In this article, we report a case of widespread and severe bilateral subcutaneous emphysema and unilateral iatrogenic pneumothorax that does not correlate with the severity of the emphysema that occurred after active CPR.